2020
DOI: 10.3233/jpd-191851
|View full text |Cite
|
Sign up to set email alerts
|

Motor Dysfunction as a Prodrome of Parkinson’s Disease

Abstract: Background Recognition of motor signs in the prodromal stage, could lead to best identify populations at risk for developing Parkinson's disease Objective This study identified motor symptoms and signs in individuals suspected of having Parkinson's disease (PD) but who did not have a progressive reduction in the speed and amplitude of finger tapping or other physical signs indicative of bradykinesia. Methods 146 patients, who had symptoms or signs suggestive of PD, were serially evaluated by a movement disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…A longitudinal study conducted in Spain showed that after 3-years of follow-up, people with essential tremor were four times more likely to develop PD than those without tremor [34] . Similar results were found in another longitudinal study, where isolated tremor was associated with a doubling of the risk of PD [35] . Rigidity is a sign not a symptom explaining why it is rarely reported by patients.…”
Section: Discussionsupporting
confidence: 90%
“…A longitudinal study conducted in Spain showed that after 3-years of follow-up, people with essential tremor were four times more likely to develop PD than those without tremor [34] . Similar results were found in another longitudinal study, where isolated tremor was associated with a doubling of the risk of PD [35] . Rigidity is a sign not a symptom explaining why it is rarely reported by patients.…”
Section: Discussionsupporting
confidence: 90%
“…Of the prediagnostic clinical manifestations, tremor showed the highest association with subsequent PD, which was also found up to 10 years before diagnosis. Various studies have reported that tremor may be an early feature of PD . In people reporting tremor years before diagnosis, one must consider the possibility that diagnosis is simply delayed in primary care.…”
Section: Discussionmentioning
confidence: 81%
“…There are, however, many reports of musculoskeletal problems, especially "frozen shoulder," before the onset of classic parkinsonian symptoms that are often attributed to local injury. While it can be argued that those are early symptoms of PD (such as decreased arm swing leading to a "frozen shoulder"), shoulder pain is now well recognized early symptom of PD [90][91][92][93][94]. Although the relationship between shoulder problems and PD is not well understood, we and others have encountered many well-documented cases of parkinsonism with onset within days or weeks following shoulder injury [16].…”
Section: Parkinsonismmentioning
confidence: 96%